Bronzino's Lodovico Capponi - Mendelsohn, Daniel Adam 1960-; Ng, Aimee (D Giles Limited, 2023)
"This latest volume in the Frick Diptych series focuses on Bronzino's "Lodovico Capponi." A text by Curator Aimee Ng is paired with a contribution from the writer Daniel Mendelsohn"--
Keywords: Bronzino, Agnolo -- 1503-1572 -- Lodovico Capponi; Bronzino, Agnolo -- 1503-1572; Bronzino, Agnolo / 1503-1572 / Lodovico Capponi; Frick Collection; Frick Collection / (OCoLC)fst00543256